How Violation of Newton’s Third Law Can Pave Way to New Space Propulsion Mechanism via Optical Diametric Drive Experiment (Bulletin of Pure and Applied Sciences – Physics, 2022)
In our initial paper discussing plausible steps toward workable warp drive  machines. The following article express our view on this debate. While there are still  objections toward existing warp drive proposals, such as by G. Landis, Harold White  etc., because they are all based on GTR, nonetheless we think it is possible by starting  to see if it is possible to deviate from Newton’s third law. And we discuss possible a  propulsion method based on negative masses, and discuss how optical diameter  drive can be first step for realistic lab-scale version of negative mass propulsion.